Water saturation effects on the tensile strength of rocks - Li, Zhihuan. (2013)
For the design of underground structures within a rock mass, the two most important parts are to find out the design stresses that the structure will withstand, as well as the design strength of the rock mass. As the tensile strength of rocks is known to be much lower than its compressive strength, it is likely that an underground structure will undergo tensile failure. However, the effects of water saturation on the tensile strength of rocks are not well researched. This study aims to determine the effects of water saturation on the tensile strength of rocks.